(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to the place and role of the parliament and its members in a modern democratic state. The analysis of the role of the deputy of the legislative chamber of the Oliy Majlis of the Republic of Uzbekistan in the implementation of democratic reforms, the legal bases of the legal status of the deputies, their participation in the legislative process, as well as in important issues in the life of the people and the state were evaluated. Also, the activity of the deputy of the State Duma of the Russian Federation, the opinions of representatives of the international legal field on the deputies, their status and activities were studied.